Blended Finance for Renewable Energy Project in PT. Sarana Multi Infrastruktur (PERSERO) Study Case: Hydroelectric and Mini Hydro Powerplant - Mahfud Gesang Nurdiyono (Eduvest - Journal of Universal Studies, 2025)
The Indonesian government’s commitment to achieving Net Zero Emissions by 2060 places a strategic focus on accelerating renewable energy development, including hydroelectric and mini-hydro power plants. Despite their potential, mini-hydro projects face numerous challenges. PT Sarana Multi Infrastruktur (Persero) (PT SMI), as a government-backed financial institution, is expected to take a catalytic role in overcoming these barriers. However, PT SMI’s portfolio in the renewable energy sector, especially in hydro projects, still have rooms for growth, requiring innovative solutions to enhance project feasibility and financing attractiveness. This research applies a mixed-methods approach, combining qualitative insights from stakeholder interviews with quantitative comparative analysis of financial ratios (IRR, NPV, DSCR, PLCR, WACC) between projects with and without blended finance. The case study focuses on eight hydro projects to simulate financing scenarios with varying degrees of blended finance application. The findings reveal that blended finance significantly improves bankability and financial feasibility, particularly for mini-hydro projects under 10 MW, by reducing the cost of capital and improving financial ratios. Projects supported by investment grants demonstrate higher DSCR and IRR, making them more attractive to private lenders. However, current limitations in grant disbursement processes, internal structuring, and pricing policy reduce the effectiveness of PT SMI’s role. The study proposes a structured bundling strategy of financial instruments and strategic plan for enhancing partnerships with strategic partners to scale up impact and strengthening PT SMI’s transformation into a development finance institution.